New Neotropical species of Lachesilla Westwood, in species group forcepeta (Psocodea: ‘Psocoptera’: Lachesillidae) - Aldrete, Alfonso N. García; Da Silva-Neto, Alberto Moreira (Zootaxa, 2020)
Eight species of Lachesilla, in species group forcepeta, are described and illustrated: three species from Costa Rica (Lachesilla herediana n. sp., Lachesilla raravis n. sp., and Lachesilla ticana n. sp.), one species from Costa Rica and Panama (Lachesilla odontiforceps n. sp.), one species each from Brazil (Lachesilla oriximinaensis n. sp.), Mexico (Lachesilla concaensis n. sp.) and Panama (Lachesilla albrookensis n. sp.), and one species from Guatemala, Mexico and Panama (Lachesilla tenuidenticulata n. sp.). The location of the types is indicated in each description.